Management Interventions For Enhancing Emotional Regulation In Children With Autism Spectrum Disorders: Scoping Review - Anggi Luckita Sari; Heni Purwaningsih; Nurul Istiqomah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Introduction: Autism Spectrum Disorder (ASD) presents significant challenges in emotional regulation, often leading to behavioral difficulties such as anger outbursts, tantrums, and depression, particularly in early childhood development. Recognizing the need for effective interventions. Objective: To explore management interventions to improve emotion regulation for children with ASD. Methods: We conducted a review of interventions to improve emotion regulation for children with ASD. The search process uses appropriate populations, concepts, and contexts. The search was carried out through the PubMed, Science direct, ProQuest, and SAGE Journal databases published between 2011 - 2021. The selection process was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Critical assessment using The Joanna Briggs Institute checklist. Results: Of 4,157 articles, 7 articles were selected for this review. Several interventions to improve emotional regulation that can be used include Cognitive behavior therapy (CBT), Physical Activity, Stress and Anger Management Program (STAMP), and Stress and Anger Management Program (STAMP). In general, this intervention can be used to improve emotional regulation in children with ASD aged 4-17 years. Conclusion: All interventions can be used to improve emotional regulation in children with ASD